Thermal Stressing of Dye Sensitized Solar Cells Employing Robust Redox Electrolytes - Perganti, D.; A. G. Kontos; Stergiopoulos, T.; V. Likodimos; Farnell, J.; Milliken, D.; Desilvestro, H.; P. Falaras (Electrochimica Acta, 2015)
Robust Dye Sensitized Solar Cells have been prepared employing liquid electrolytes using ethyl isopropyl sulfone (EiPS) high boiling point solvent. The cells were tested for their durability under harsh thermal stressing conditions of 85 °C and prolonged ageing time, 3000 h in the dark. The use of EiPS outperforms stability-wise the typical methoxypropionitrile MPN solvent, improving the cell stability from 38 to 75%. For both solvents, the physicochemical analysis infers the thermal degradation of the cell with the main changes occurring in the first 300 h of ageing. This was attributed to partial triiodide loss which reduces short circuit photocurrent and leads to formation of luminescent species in the electrolyte that affects the TiO2 surface and reduces open circuit photovoltage. The degradation effects were notably supressed by the use of the more stable EiPS solvent, where it was possible to optimize the iodine content in the redox mediator. It has been thus confirmed that iodine concentration as low as 0.05 M in the EiPS electrolyte is slightly preferable in terms of stability and device performance, comparing with higher concentrations, 0.1 and 0.15 M, respectively. © 2015 Elsevier Ltd. All rights reserved.
cited By 12